We know the series-expansion for these "sum of powers":

$$\sum_{i=0}^n i = \frac{n(n+1)}{2} = \frac{1}{2}n^2+\frac{1}{2}n$$ $$\sum_{i=0}^n i^2 = \frac{n(n+1)(n+2)}{6} = \frac{1}{3}n^3+\frac{1}{2}n^2+\frac{1}{6}n$$ $$\sum_{i=0}^n i^3 = \frac{n^2(n+1)^2}{4} = \frac{1}{4}n^4+\frac{1}{2}n^3+\frac{1}{4}n^2$$ $$...$$ But can we come up with a general formula? $\sum_{i=0}^n i^P =$ "Compact form" = "Series form"
Using Mathematica, I generated sums of higher powers to look for overall patterns in the coefficients and the polynomials. I could not find anything significant in the "compact form" but I found several in the "series form." Take a look: Series expansion formula for sum of powers from P=1 to P=15 ;; Coefficients only
So what I found was that the "sum of powers" formula has this general equation $S(n)=An^{P+1}+Bn^P+Cn^{P-1}+Dn^{P-2}+...+En $. If we include the fact that some of the coefficients are $0$, then there are $P+1$ terms in this polynomial equation. I was tackling this problem with the assumption that $P$ was a natural number but it turns out that this general equation is valid for any real number $P$. Also, the general series expansion formula is equivalent to the series expansion for the generalized harmonic number (https://en.wikipedia.org/wiki/Harmonic_number).
Anyway, here are the patterns I found in the coefficients: $$A = \frac{1}{P+1}, B=\frac{1}{2}, C=\frac{P}{12} $$ $D=0$ and every second letter after D is $0$.
$$E=\frac{-P(P-1)(P-2)}{720}, G=\frac{P(P-1)(P-2)(P-3)(P-4)}{720},$$ $$I=\frac{-P(P-1)(P-2)(P-3)(P-4)(P-5)(P-6)}{1209600},...$$
And so on. It appears that for every coefficient letter, this is the numerator: $$\frac{P!(-1)^{0.5k+1.5}}{(P-k)!}$$ where k is the $k^{th}$ letter after B with k starting at 1 (and k is odd in this formula since every second letter after D is $0$). But where does the denominator come from? If you examine more coefficient letters, the denominator seems to be growing exponentially (factorial?), but that is all I could find. $$$$
Update! I later found the generalized formula here: https://en.wikipedia.org/wiki/Faulhaber%27s_formula. This is what the denominator equals: $$\frac{(k+1)!}{|B(k+1)|}$$ Amazing how the Bernoulli numbers belong in this formula. That explains the alternating sums and the coefficients of $0$. So here is the complete equation: $$\sum_{i=0}^n i^P =\frac{1}{P+1}n^{P+1}+\frac{1}{2}n^P+\sum_{k=1}^{P-1} \frac{B(k+1)P!}{(P-k)!(k+1)!}n^{P-k}$$ This can be further condensed, assuming $B(1)=+\frac{1}{2}$: $$\sum_{i=0}^n i^P =\sum_{k=-1}^{P-1} \frac{B(k+1)P!}{(P-k)!(k+1)!}n^{P-k}$$

Interesting. The equation kind of resembles the binomial expansion formula (https://en.wikipedia.org/wiki/Binomial_theorem). But why do the Bernoulli numbers appear in this formula? I looked at several sites (https://en.wikipedia.org/wiki/Bernoulli_number, http://math.ucr.edu/~res/math153/s12/bernoulli-numbers.pdf, https://ncatlab.org/nlab/show/Bernoulli+number), but the explanations are not intuitive. From what I see it, "they just do" but I do not understand why. Let me know if there are any mistakes with my equations or if there is anything I am missing.


Consider the identity $$1+e^{x} +e^{2x}+\ldots+e^{nx}=\frac{e^{(n+1)x}-1}{e^x-1}= \frac{e^{(n+1)x}-1}{x}\frac{x}{e^x-1}$$ for power series and note that $$\frac{x}{e^x-1}=\sum_{k=0}^\infty\frac{B_k}{k!}x^k.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.